2001
DOI: 10.1016/s0925-4773(01)00324-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative expression studies of aldolase A, B and C genes in developing embryos and adult tissues of Xenopus laevis

Abstract: We previously cloned cDNAs for all the members (A, B and C) of Xenopus aldolase gene family, and using in vitro transcribed RNAs as references, performed quantitative studies of the expression of three aldolase mRNAs in embryos and adult tissues. A Xenopus egg contains ca. 60 pg aldolase A mRNA and ca. 45 pg aldolase C mRNA, but contains only ca. 1.5 pg aldolase B mRNA. The percent composition of three aldolase mRNAs (A:B:C) changes from 56:1.5:42.5 (fertilized egg) to 54:10:36 (gastrula), to 71:14.5:14.5 (neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Aldolase is an important enzyme in glycolysis; the three vertebrate homologs have been cloned in humans (Besmond et al, 1983), mice (Tsutsumi et al, 1983(Tsutsumi et al, , 1984, and Xenopus (Atsuchi et al, 1994;Hikasa et al, 1997;Kajita et al, 2001). In the present study, we isolated the aldolase A, B, and C genes in grass carp and characterized their expression.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Aldolase is an important enzyme in glycolysis; the three vertebrate homologs have been cloned in humans (Besmond et al, 1983), mice (Tsutsumi et al, 1983(Tsutsumi et al, , 1984, and Xenopus (Atsuchi et al, 1994;Hikasa et al, 1997;Kajita et al, 2001). In the present study, we isolated the aldolase A, B, and C genes in grass carp and characterized their expression.…”
Section: Discussionmentioning
confidence: 80%
“…Besides, upregulation of the aldolase A and C genes and downregulation of aldolase B gene have been observed in the hepatic tissue of liver cancer patients (Schapira et al, 1963). Aldolase A, B, and C genes have been isolated from amphibian species such as Xenopus laevis (Atsuchi et al, 1994;Hikasa et al, 1997;Kajita et al, 2001) and their spatial and temporal expression patterns have been characterized (Kajita et al, 2001). The aldolase B gene in fish has been cloned in bream (Llewellyn et al, 1995) and salmon (Llewellyn et al, 1998), while the aldolase C gene has been cloned in goldfish (Berardini et al, 1997); however, there have been no reports on the cloning of all three aldolase genes in a single fish species.…”
Section: Introductionmentioning
confidence: 99%
“…A Xenopus fertilized egg contained approximately 60 pg of aldolase A mRNA, 45 pg of aldolase C mRNA but only 1.5 pg or less aldolase B mRNA. Thus, aldolase A and C Fig 3. Expression of three aldolase mRNAs in developing embryos from Kijita et al [17]. Size of the circle is comparable among different stages.…”
Section: Expression Of Three Aldolase Mrnas In Oocytes and Embryosmentioning
confidence: 90%
“…We obtained a cell line from Xenopus adult kidney and Fluorescence in situ hybridization (FISH) studies showed that the three aldolase genes are located on different chromosomes [17].…”
Section: Cloning Of Xenopu S Aldolases a B And C Cdnasmentioning
confidence: 99%
See 1 more Smart Citation